Violations of the freedom of conscience in the Donbass - Ismagilov, Said (Relihijna svoboda, 2016)
After part of the territory of Donetsk and Lugansk regions in 2014 came under the control of separatist entities supported by the Russian Federation, the situation with respect for human rights and freedoms, including the right to freedom of conscience, became much more complicated. First of all, it can be noted that the beginning of repressions on a religious basis laid a wide and intensive use of religious rhetoric in mobilizing supporters of "L / DPR", in connection with which believers of confessions and denominations considered harmful by Orthodox fundamentalists were systematic persecution and spontaneous acts of aggression.